2011
DOI: 10.1109/jlt.2011.2157893
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Single-Polarization Single-Mode Microstructured Polymer Optical Fiber

Abstract: A new procedure to obtain single-polarization singlemode polymeric optical fibers is reported. The selective polarization confinement loss mechanism is obtained by applying external hydrostatic pressure in a specially designed side-hole microstructured polymer optical fiber. It is shown that, at nm, pressure around 380 bar allows inducing confinement loss as high as 35 dB/m for one polarization state while the other is guided with low loss ( dB/m). The loss mechanism is shown to be related to coupling between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Other methods for obtaining polarizing PCFs have also been studied [11][12][13][14]. Espinel et al [15] numerically showed a microstructured polymer fiber for which the application of hydrostatic pressure induced birefringence and polarizing action. The obtained PDL was of the order of 0.38 dB/cm.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods for obtaining polarizing PCFs have also been studied [11][12][13][14]. Espinel et al [15] numerically showed a microstructured polymer fiber for which the application of hydrostatic pressure induced birefringence and polarizing action. The obtained PDL was of the order of 0.38 dB/cm.…”
Section: Introductionmentioning
confidence: 99%
“…2.2 se mostra o índice efetivo e a perda por confinamento em função do comprimento de onda para a fibra proposta em [34], a É importante notar que na maioria dos trabalhos ligados com PCF de única polarização somente se faz uso da liberdade que se tem na geometria da fibra e da escolha do material (polimetilmetacrilato ou sílica), para obter a propriedade de única polarização [34], [37]- [39], ignorando a influência que a inclusão de perturbações externas, como curvaturas ao longo da fibra [35], pressão hidrostática ou forças pontuais no contorno externo da fibra poderia ter no controle ativo dessa propriedade óptica. Motivados por esse fato, se quer mostrar nesta seção o uso do novo grau de liberdade mecânico, visto como uma pressão hidrostática externa, em uma fibra PCF para a obtenção e sintonização ativa do seu estado de única polarização [40], [41].…”
Section: Pcf Em Pmma Sob Pressão Externaunclassified